Economic Losses From Marine Pollution - Ofiara Douglas D. (Island Press, 2001)
Marine pollution causes significant damage to fisheries and other economically productive uses of the ocean. The value of that damage can be quantified by economists, but the meanings of those valuations and how they are derived are often obscure to noneconomists.